2007
DOI: 10.1002/eji.200636900
|View full text |Cite
|
Sign up to set email alerts
|

CD8α/α homodimers fail to function as co‐receptor for a CD8‐dependent TCR

Abstract: In this study, we have started to dissect the molecular basis of CD8 dependence of a high and low avidity CTL clone specific for the same peptide epitope. Using anti-CD8a and anti-CD8b antibodies, we found that cytotoxicity and IFN-c production by high but not by low avidity CTL was strongly CD8 dependent. We isolated the TCR genes of both types of CTL clones and used retroviral gene transfer to analyse the function of these TCR in primary T cells of wild-type and CD8b-deficient mice. Both TCR triggered antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
(31 reference statements)
1
31
0
Order By: Relevance
“…2C). While physiologically CD8αα is non-identical to the natural CD8αβ heterodimer (McNicol et al, 2007), its binding to MHC I mimics one of the two proposed modes of the CD8αβ binding (Chang et al, 2006) and is capable of antagonizing the latter (Sewell et al, 1999). The peptidespecific binding of TCR is unaffected by the bound CD8αα .…”
Section: Discussionmentioning
confidence: 99%
“…2C). While physiologically CD8αα is non-identical to the natural CD8αβ heterodimer (McNicol et al, 2007), its binding to MHC I mimics one of the two proposed modes of the CD8αβ binding (Chang et al, 2006) and is capable of antagonizing the latter (Sewell et al, 1999). The peptidespecific binding of TCR is unaffected by the bound CD8αα .…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the CD8b tail eliminates all phosphorylation of CD3f, and Zap70 [98]. It has recently been shown that the aa homodimer cannot substitute for CD8ab heterodimer [99]. Thus, both chains of the heterodimer are important for location and proper function.…”
Section: Genetic Structurementioning
confidence: 99%
“…(iv) TCR sequences have been shown to convey CD8 dependence (2,14,(17)(18)(19)(20). (v) The TCR of a CD8-independent CTL engaged its ligands in a noncanonical docking orientation (23).…”
Section: +mentioning
confidence: 99%
“…However, other studies claim that CD8 dependence is related to TCR sequences and that CD8-independent T cells can express lowaffinity TCR (2,(17)(18)(19)(20). This latter view is supported by the observations that CD8 independence or dependence can be conveyed by TCR gene transfer (18,20) and that the TCR repertoires of CD8-independent, virus-specific CTL from CD8β-or CD8α-KO mice are different from TCR repertoires of such CTL from normal mice (2,14,17). CD8 + (and CD4 + ) T cells are generated by a multistep process in the thymus.…”
mentioning
confidence: 99%